Embracing the unpredictable. Leadership, learning, changing practice. Issue 5 (19th October 2016) - Brinck, Lars; Tanggaard, Lene
Abstract : What is good and effective leadership? And how do we learn to become such productive and even innovative leaders? This paper will argue that dissolving conventional hegemonies of what constitutes true leadership, embracing the unforeseen of everyday work practices, and regarding diversity as an important resource may prove to show new paths for leadership development. Many scholars and leaders have looked in the direction of situated learning theory to develop our understanding of good leadership. The study's literature review reveals on one hand a body of pre- and descriptive applications of situated learning theory shadowing analytic potential. On the other hand, it reveals a line of substantial analytical contributions to the field of leadership development. Analysing two empirical leadership cases through the lens of situated learning theory, the study unfolds examples of 'losing control' and letting practice itself lead the way. Learning to become (more of a) leader seems to constitute an integral part of everyday changing practice. The study illuminates an unexploited potential for enhancing our analytic focus on the improvisational, diverse, and non-hegemonic aspects of leadership practice and on how this is developed: leadership 'embracing the unpredictable'.